2017
DOI: 10.3171/2016.10.jns16748
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and outcomes after aneurysmal subarachnoid hemorrhage: a nationwide analysis

Abstract: OBJECTIVE Although cigarette smoking is one of the strongest risk factors for cerebral aneurysm development and rupture, there are limited data evaluating the impact of smoking on outcomes after aneurysmal subarachnoid hemorrhage (SAH). Additionally, two recent studies suggested that nicotine replacement therapy was associated with improved neurological outcomes among smokers who had sustained an SAH compared with smokers who did not receive nicotine. METHODS Patients who underwent endovascular or microsurgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 50 publications
(40 reference statements)
4
28
1
Order By: Relevance
“…Presently, smokers were younger than nonsmokers. The difference was though less than in earlier studies reporting smokers to be 5-10 years younger than nonsmokers at the onset of their hemorrhage [7,44,59]. Aneurysm location was very similar in smokers and nonsmokers, and overall, our material shows the same distribution as that found in recent series [11,50], but ruptured aneurysm in the vertebrobasilar circulation was more common in our cohort than in that reported by Hammer at al.…”
Section: Patients and Entry Variablessupporting
confidence: 56%
See 3 more Smart Citations
“…Presently, smokers were younger than nonsmokers. The difference was though less than in earlier studies reporting smokers to be 5-10 years younger than nonsmokers at the onset of their hemorrhage [7,44,59]. Aneurysm location was very similar in smokers and nonsmokers, and overall, our material shows the same distribution as that found in recent series [11,50], but ruptured aneurysm in the vertebrobasilar circulation was more common in our cohort than in that reported by Hammer at al.…”
Section: Patients and Entry Variablessupporting
confidence: 56%
“…With such long-lasting impact of smoking on the natural history of intracranial aneurysms, one cannot exclude that also the protective effects persist over some time. This is partly supported by former smokers faring slightly better on some measures than never-smokers in the study of Dasenbrock et al [7].…”
Section: Management and Complicationsmentioning
confidence: 78%
See 2 more Smart Citations
“…Two recent hospital-based studies reported that smokers and those with history of hypertension have better survival after aneurysmal subarachnoid hemorrhage (aSAH), 2,3 even though these two factors are considered the main risk factors for aSAH. 1 It is important to recognize that these studies included only hospital-admitted early aSAH survivors and excluded the sudden-death aSAH individuals that, among all aSAH cases, account for approximately 25%.…”
Section: Introductionmentioning
confidence: 99%